PHARMACOLOGICAL EVALUATION OF ANTIDIABETIC EFFECT OF ETHYL ACETATE EXTRACT OF TEUCRIUM STOCKSIANUM BOISS IN ALLOXAN-INDUCED DIABETIC RABBITS - Alamgeer; M. Rashid; M. N. Mushtaq; M. N. H. Malik; S. A. Ghumman; M. Numan; A. Q. Khan M. O. Omer; H. M. Tahir (Journal of Animal and Plant Sciences, 2013)
Teucrium stocksianum Boiss has been used for the treatment of diabetes in folklore. Present study was designed to evaluate the effect of ethyl acetate extract of Teucrium stocksianum on blood glucose level in alloxan induced diabetic rabbits. The ethyl acetate extract produced significant (P<0.001) decrease in blood glucose level, ALT, AST, ALP, triglycerides, cholesterol, LDL, VLDL levels and T.C/HDL cholesterol ratio in diabetic treated rabbits as compared to diabetic control whereas, the HDL levels of diabetic treated rabbits were significantly (P<0.001) increased. It is concluded that ethyl acetate extract of Teucrium stocksianum possesses hypoglycaemic, hypolipidemic and hepatoprotective effects in alloxanized rabbits which strengthens its traditional use in diabetes
Keywords: Alloxan; hepatoprotection; hyperglycaemia; hypolipidemia; Teucrium stocksianum